2004
DOI: 10.1021/tx049818e
|View full text |Cite
|
Sign up to set email alerts
|

5‘-(2-Phosphoryl-1,4-dioxobutane) as a Product of 5‘-Oxidation of Deoxyribose in DNA:  Elimination as trans-1,4-Dioxo-2-butene and Approaches to Analysis

Abstract: Oxidation of deoxyribose in DNA leads to the formation of a spectrum of electrophilic products unique to each position in the sugar. For example, chemical reactions following abstraction of the C5‘-hydrogen atom partition to form either a nucleoside 5‘-aldehyde residue attached to the 5‘-end of the DNA strand or a 5‘-formyl phosphate residue attached to the 3‘-end of the DNA strand that is accompanied by a four-carbon fragment on the 5‘-end. We now present two approaches that both identify the latter fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…The instability of the oxAB (t 1/2 ~20 hr at 37 °C; refs. 39,44) necessitated chemical stabilization in quantitative fashion, so we chose to convert it to a stable 3′-pyridazine moiety by derivatization with hydrazine as originally described by Hecht and coworkers (45) Each of the steps in the method was optimized for parameters such as concentration, reaction time, temperature and pH, as previously described (34). The ethyl acetate extraction of HMP (3X, pH 7) was 99.5% efficient and silylation was most efficient at 25 °C and 30 min reaction time with ratios of ethyl acetate to BSTFA between 50:50 to 70:30; there was a significant reduction in silylation when ethyl acetate was reduced below 30% (data not shown).…”
Section: Development and Optimization Of A Gc/ms Methods To Quantify Tmentioning
confidence: 99%
“…The instability of the oxAB (t 1/2 ~20 hr at 37 °C; refs. 39,44) necessitated chemical stabilization in quantitative fashion, so we chose to convert it to a stable 3′-pyridazine moiety by derivatization with hydrazine as originally described by Hecht and coworkers (45) Each of the steps in the method was optimized for parameters such as concentration, reaction time, temperature and pH, as previously described (34). The ethyl acetate extraction of HMP (3X, pH 7) was 99.5% efficient and silylation was most efficient at 25 °C and 30 min reaction time with ratios of ethyl acetate to BSTFA between 50:50 to 70:30; there was a significant reduction in silylation when ethyl acetate was reduced below 30% (data not shown).…”
Section: Development and Optimization Of A Gc/ms Methods To Quantify Tmentioning
confidence: 99%
“…As shown in Scheme 1, the chemistry of 5′-oxidation of deoxyribose in DNA by a variety of DNA-cleaving agents, including enediynes (8) and manganese porphyrins (9), partitions to form strand breaks containing 3′-phosphate and 5′-nucleoside-5′-aldehyde residues, or a 3′-formylphosphate species accompanied by a four-carbon fragment that we and others have identified as a 5′-(2-phosphoryl-1,4-dioxobutane) residue (7,10). We recently showed that this dialdehydic residue undergoes β-elimination to form trans-1,4-dioxo-2-butene (7), a highly reactiveα,β-unsaturated dicarbonyl species.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The trans isomer ( trans - 1 ), which also forms adducts with nucleotides in DNA, is released from 5′-(2-phosphoryl-1,4-dioxobutane) (DOB), an oxidized abasic lesion resulting from C5′-hydrogen-atom abstraction. [8,11] The DOB lesion is produced by several antitumour agents and by γ radiation. [1114] This lesion is a potent irreversible inhibitor of DNA polymerase β, an enzyme that is a primary component of base excision repair that is overexpressed in many cancers.…”
mentioning
confidence: 99%
“…[8,11] The DOB lesion is produced by several antitumour agents and by γ radiation. [1114] This lesion is a potent irreversible inhibitor of DNA polymerase β, an enzyme that is a primary component of base excision repair that is overexpressed in many cancers. [1519] Hence, DOB formation may provide a chemical basis for the potent cytotoxicity of the antitumor agents that produce it.…”
mentioning
confidence: 99%